Dental measurements of Deuteromalayid Javanese students of the Faculty of Dentistry Airlangga University - Myrtati Dyah Artaria; Bambang Soegeng Herijadi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2011)
Background: Dental anthropology is a new field of study in Indonesia, hence there are few numbers of research that can be found in this field. Knowledge in this field is needed due to the large area and diversity of the people. Moreover, knowledge regarding the possibility to differentiate the sexes of skeletons is still needed for the purpose of identification. Purpose: This research intended to study the differences in mesio-distal measurements of the teeth of Deuteromalayid Javanese males and females studying in the Faculty of Dentistry in Airlangga University. Methods: This study used mesiodistal metric dental data, using dental caliper, to test the existence of sexual dimorphism. Sample were teeth of freshman students of the Airlangga University, from 52 individuals comprising 26 males and 26 females Deuteromalayid originated from Java (Indonesia) studying in the Faculty of Dentistry Airlangga University. Measurements were not performed on damaged casts due to caries or other reasons. Differences between males and females were tested using independent t-test. Results: The mean of mesiodistal measurements in males and females differs, where the males have greater size of mesiodistal measurements. The results showed that there were significant differences between sexes in the sample, in all field of teeth except the second upper and lower premolars. Reverse sexual dimorphism-female teeth measurement is larger than those of males-has not been found in these samples. The result of this study revealed that the range of mesiodistal measurements of every tooth in males and females overlapped. Conclusion: It is concluded that teeth measurement of males is bigger than females, except maxillary and mandibular second premolars. Latar belakang: Antropologi dental adalah bidang studi baru di Indonesia, dan karenanya penelitian di bidang ini masih sedikit dijumpai di Indonesia. Apalagi masih dibutuhkan pengetahuan mengenai apakah jenis kelamin dapat dilihat dari geligi tengkorak manusia, untuk keperluan identifikasi. Tujuan: Tujuan penelitian ini adalah untuk mengetahui perbedaan ukuran mesiodistal gigi antara laki-laki dan perempuan Deuteromalayid dari Jawa. Metode: Penelitian ini menggunakan data pengukuran mesio-distal gigi untuk mengetahui apakah ada perbedaan antar jenis kelamin pada ukuran gigi mahasiswa Fakultas Kedokteran Gigi Universitas Airlangga keturunan Deuteromalayid dari Jawa. Penelitian ini merupakan penelitian tahap awal dengan jumlah sampel yang masih terbatas. Sampel diambil dari 52 orang individu yang bersedia dicetak giginya dengan jumlah 26 laki-laki dan 26 perempuan. Pengukuran dilakukan dari mesial ke distal gigi. Pengukuran tidak dilakukan mesial gigi yang mengalami kerusakan seperti misalnya karena karies atau aus yang parah. Signifikansi perbedaan antar jenis kelamin dianalisis menggunakan independent t-test. Hasil: Hasil penelitian menunjukkan bahwa terdapat perbedaan yang signifikan antar laki-laki dan perempuan di semua jenis gigi, kecuali pada premolar ke dua atas dan bawah. ”Reverse sexual dimorphism” di mana rata-rata ukuran gigi perempuan lebih besar dari lakilaki, tidak ditemukan pada sampel ini. Pada penelitian ini meskipun dijumpai ”overlap” pada ukuran gigi laki-laki dan perempuan, tetapi sebagian besar rata-rata ukuran gigi berbeda secara bermakna antar kedua jenis kelamin pada sampel mahasiswa Fakultas Kedokteran Gigi Universitas Airlangga yang berasal dari Jawa keturunan Deuteromalayid. Kesimpulan: Dapat disimpulkan bahwa pengukuran gigi laki-laki lebih besar daripada perempuan, kecuali premolar kedua maksila dan mandibula.